1999
DOI: 10.1046/j.1365-2400.1999.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eutrophication on fish and fisheries in Finnish lakes: a survey based on random sampling

Abstract: The effects of eutrophication on fish and fisheries in Finnish lakes were determined by an extensive lake survey conducted in 1995 and 1996. The study lakes (873) were chosen by stratified random sampling from all Finnish lakes with a surface area ≥ 0.04 km2 (29 515 lakes in all). The chemical parameters of the lake water were determined for water samples taken in autumn 1995. Information on the fish stocks of the study lakes was collected by means of a postal questionnaire sent to local fishing authorities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 12 publications
2
63
0
Order By: Relevance
“…On the other hand, fish in the Jurumirim Reservoir region is sold in cities near the reservoir, where the supply of fish is low and, consequently, the price increases. With respect to environmental issues, in Finland, for example, eutrophic lakes are generally associated with a devaluation of fish prices and exotic species also have a low market value (Tammi et al, 1999). A similar finding was reported in northeast Brazil (Attayde et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On the other hand, fish in the Jurumirim Reservoir region is sold in cities near the reservoir, where the supply of fish is low and, consequently, the price increases. With respect to environmental issues, in Finland, for example, eutrophic lakes are generally associated with a devaluation of fish prices and exotic species also have a low market value (Tammi et al, 1999). A similar finding was reported in northeast Brazil (Attayde et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…a For details on the use of capture techniques, see Novaes & Carvalho (2009, 2011 (De Silva et al, 2004). A number of research projects have indicated that, in Brazil and in other countries, the fish catch has shown declines several years after the introduction of such species (Tammi et al, 1999;ECO -AES Tietê, 2001;Wolos et al, 2009;Attayde et al, 2011;Han & Dumont 2011). The negative impacts of species introductions on native species, as well as the association between the tilapia and eutrophication, has been demonstrated in many studies (including Starling et al, 2002;Figueredo & Giani, 2005;Attayde et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was also strongly related to environmental gradients, with species richness increasing with lake size and conductivity, whereas taxonomic distinctness was related to factors portraying lake productivity and perhaps was also associated with an increase in habitat heterogeneity in terms of increasing macrophyte cover and diversity from oligotrophic to mesoeutrophic conditions (Rørslett 1991). As high-productivity lakes in boreal and temperate regions are typically dominated by cyprinids (e.g., Tammi et al 1999;Jeppesen et al 2000), instead of species divided equally among several families and orders, productivity may actually decrease taxonomic distinctness, while species richness may either increase or remain unchanged with productivity compared to lower productivity conditions. The pattern was rather different in the other species-poor fish data set, however; in fact, an opposite pattern was found for one data set of stream diatoms, in which species richness and taxonomic distinctness were positively related.…”
Section: Discussionmentioning
confidence: 96%
“…Decreases in hypolimnetic oxygen concentrations have direct negative effects on fish that physiologically require oxygenated cold water to survive, grow, and reproduce. Cultural eutrophication has caused declines in many European and North American coldwater fish populations (Hasler 1947, Tammi et al 1999. Latta (1995) reported that cisco (Coregonus artedii) have been extirpated in at least 14% of Michigan lakes, primarily from eutrophication.…”
mentioning
confidence: 99%